Revisiting self-regulatory techniques to promote physical activity in older adults: null-findings from a randomised controlled trial*. Issue 10 (2nd October 2016) - Warner, Lisa M.; Wolff, Julia K.; Ziegelmann, Jochen P.; Schwarzer, Ralf; Wurm, Susanne
Abstract : Objective . A randomised controlled trial (RCT) was conducted to evaluate a three-hour face-to-face physical activity (PA) intervention in community-dwelling older German adults with four groups: The intervention group (IG) received behaviour change techniques (BCTs) based on the health action process approach plus a views-on-ageing component to increase PA. The second intervention group 'planning' (IGpl) contained the same BCTs, only substituted the views-on-ageing component against an additional planning task. An active control group received the same BCTs, however, targeting volunteering instead of PA. A passive control group (PCG) received no intervention. Design. The RCT comprised 5 time-points over 14 months in N = 310 participants aged 64+. Main outcome measures. Self-reported as well as accelerometer-assessed PA. Results. Neither PA measure increased in the IG as compared to the other groups at any point in time. Bayes analyses supported these null-effects. Conclusion. A possible explanation for this null-finding in line with a recent meta-analysis is that some self-regulatory BCTs may be ineffective or even negatively associated with PA in interventions for older adults as they are assumed to be less acceptable for older adults. This interpretation was supported by observed reluctance to participate in self-regulatory BCTs in the current study.